Semai children in Cameron Highland and understanding the indigenous childrens rights in the International Legal Setting / Mohamad Sabri Yusof - Yusof, Mohamad Sabri (Universiti Teknologi MARA, Pahang, 2017)
Adults and parents perceives that under the law they are having full authority to decide what is best for the children without realizing that the children themselves have also rights to decide what is best for them. The same perception appears in the family circle of the Semai and other indigenous people in general. This paper tries to bring adult and parents alike to come to terms some of the minimum rights provided to the children around the world including the indigenous children under International Law so that one are not caught unaware and help secure the very basic needs of children of today.